The effects of heat and water stress toward crop growth and yield of Oryza sativa L. / Mohamed Izwan Baharin - Baharin, Mohamed Izwan (Faculty of Plantation and Agrotechnology, 2019)
The abiotic factors such as heat and water stress experienced during paddy cultivation believed had significant effect on the growth and productivity of paddy. The plants will respond toward the stress in order to assimilate with the situation faced. The adjustment and assimilation of plant toward the stress condition caused the inhibition in crop growth performance and production of yield. This review provided the effects and interactions between heat & water stress with the measured crop growth characters and production of yield from previous studies from dependable researchers. The heat and water stress condition experienced during growing stages of paddy such as, tillering, panicle initiation, flowering and milky stage have their own specific effects. The effects of stresses studied were reduction in grain yield, the weight of a total of grains and percentage of grain yield reduced compared with the normal temperature of rice cultivation. This review showed the most stress-sensitive stages for both kinds of stresses. In terms of crop growth characters and yield production, both stress proved most affecting the Oryza sativa L. during flowering stages. The effects and interaction of water and heat stress were reviewed in separate parts to extract clearer results. While for the heat stress interaction with particulars measured were reviewed using two different percentages (40% and 60%) of water stress to observe the interaction of crop growth performance and yield parameters. All the result from the previous researches reviewed were specifically on low-land rice or irrigated field rice varieties.